Known and Unknown Aspects of Workplace Bullying: A Systematic Review of Recent Literature and Future Research Agenda. (September 2020) - Gupta, Parul; Gupta, Urvashi; Wadhwa, Simran
Last decades showed a high interest in studying the workplace bullying (WB) phenomenon in a variety of disciplines and in a number of WB areas such as concepts and forms of WB, antecedents and consequences of WB, WB interventions, etc. This study offers classification and description of current WB literature, and identifies research gaps to be bridged by further empirical research. In the first part, authors systematically review 167 refereed journal articles, classify the WB research into five main research themes and summarize their findings. In the second part, the article uncovers various unknown aspects of WB and provides concrete directions for future empirical research. Thrust areas of attention are highlighted for industry and policy makers.